Dynamic multiple-scattering treatment of X-ray absorption: Parameterization of a new molecular dynamics force field for myoglobin - Chillemi, Giovanni (Struct Dyn, 2018)
We present a detailed analysis of the X-ray absorption near-edge structure (XANES) data on the Fe K-edge of CO Myoglobin based on a combined procedure of Molecular Dynamics (MD) calculations and MXAN (Minuit XANes) data analysis that we call D-MXAN. The ability of performing quantitative XANES data analysis allows us to refine classical force field MD parameters, thus obtaining a reliable tool for the atomic investigation of this important model system for biological macromolecules. The iterative procedure here applied corrects the greatest part of the structural discrepancy between classical MD sampling and experimental determinations. Our procedure, moreover, is able to discriminate between different heme conformational basins visited during the MD simulation, thus demonstrating the necessity of a sampling on the order of tens of nanoseconds, even for an application such X-ray absorption spectroscopy data analysis.